6-Bromo-1-(1,2-propadienyl)-3-(2-propynyl)-1H-imidazo[4,5-b]pyridin-2( 3H)-one - Dahmani, S.; Haoudi, A.; Capet, F.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The reaction of propargyl bromide and 6-bromo-1,3-dihydroimidazo [4,5-b] pyridin-2-one in refluxing dimethylformamide yields the title compound, C(12)H(8)BrN(3)O, which features nitrogen-bound propadienyl and propynyl substituents. The imidazolopyridine fused ring is planar (r.m.s. deviation = 0.012 angstrom); the propadienyl chain is coplanar with the fused ring as it is conjugated with it, whereas the propynyl chain is not as the nitrogen-bound C atom is a methylene linkage. The acetylenic H atom is hydrogen bonded to the carbonyl O atom of an adjacent molecule, forming a helical chain runnning along the b axis.